Exploring supply chain flexibility in a FMCG food supply chain. Issue 3 (September 2016) - Manders, Jorieke H.M.; Caniëls, Marjolein C.J.; Ghijsen, Paul W. Th.
Abstract: Empirical studies about supply chain flexibility have mainly focused on one (manufacturing) company, occasionally incorporating the adjoining view from a supplier, distributor, or retailer. The present paper argues that a dyadic perspective is not sufficient and that an integrated perspective is required. In-depth case study data was collected and analyzed. The data covers eight organizations in a fast-moving consumer goods (FMCG) food supply chain, including suppliers, the main manufacturer, the logistics service provider, and retailers. Drawing on network theory and stakeholder theory, the study analyzed how these eight organizations experience flexibility across the supply chain. The findings show that each chain member implements flexibility to fulfill the direct needs of the next-tier chain member. Organizations at different positions in the supply chain prioritize other flexibilities. There is no support for overall supply chain flexibility. Highlights: We examine supply chain flexibility from the view of eight supply chain members. Our study shows which flexibilities are prioritized at different time horizons. Forward and backward integration is not enough to achieve SC flexibility. Organizations at diverse positions in the supply chain prioritize other flexibilities. There is no support for overall supply chain flexibility.